Optimizing the potential benefits from the African Continental Free Trade Area Agreement (AfCTA) in the West African Monetary Zone through enterprise development - Eunice N. Egbuna; Maimuna John-Sowe; Dauda Mohammed; Hissan Abubakari; Eric Sambolah; Komay Adams (West African Monetary Institute (WAMI), 2020)
Studies have shown that trade relationships among countries in Africa including intra-regional groupings such as the West African Monetary Zone (WAMZ) is low. Therefore, intra-trade becomes critical in unlocking the growth potentials of the continent and its regional groupings. Taking cognizance of the importance of intra-trade, African leaders came up with the idea to float the African Continental Free Trade Area (AfCFTA) in order to foster trade integration, which could help boost economic development in the continent. Its objective is to promote Africa intratrading relationships by facilitating the removal of tariffs on up to 90.0 percent of products traded among countries and address other non-tariff barrier issues. The main objective of this paper is to provide strategies that would provide a guidepost for private sector growth and development to enable them maximize the benefits of the AfCTA initiative. SMEs are important drivers of trade; hence, their growth and innovation could greatly accelerate the aspiration of the AfCTA initiatives. Due to the effect of COVID-19 pandemic leading to restrictions in movements, and lockdown, the authors adopted a descriptive and an exploratory analysis approach using the WAMI Trade Integration Index and World Bank Enterprise survey. The paper uncovered that access to Finance, infrastructure deficiency (electricity), high tax, political instability, crime, general insecurity within the region as well as corruption are the major impediment to SMEs growth in the WAMZ. The paper recommends the creation of development finance unit in member countries central banks, effective operationalization of private public partnership Acts, economic digitalization, and synchronization of financial governance and payments system as some of the actionable policy recommendations to the authorities of the WAMZ in order to make AfCFTA a viable venture.
Keywords: I38; R11; Y1; 330; African Continental Free Trade Area (AfCFTA); West African Monetary Zone(WAMZ); Enterprise Development